Ecological Impact of Mangrove Forest Damage on Women's Economic Resources Based on Ecofeminism Theory in Youtefa Bay, Jayapura City - Hosio, Y. Flora; Aquarista, Aquarista (Journal Of Accounting Management Business And International Research, 2022)
Youtefa Bay in Jayapura City as a bay that is famous for its beautiful natural marine scenery has been designated as a Nature Tourism Park in accordance with the Decree of the Minister of Forestry Number: 714/Kpts-II/1996 with an area of 1,675 Ha. Research on the ecological impact of the Mangrove Forest Area in Youtefa Bay with data from the Forest Area Management Center (BPKH) Region X Papua, however, the mangrove forest cover has decreased with data from 1967-2008, which is 511.24 Ha, has decreased to 241.24 Ha. Which is a habitat for shellfish in the mangrove forest area as a livelihood for women in Youtefa Bay with the impact of environmental damage to the mangrove forest. The purpose of this study is related to the ecological impact of mangrove forests on shellfish resources based on the economy of women in Youtefa Bay, Jayapura City to (1) determine the extent of direct and indirect impacts of the effects of mangrove forest damage and plastic waste for women seeking shellfish as household income. (2) examine the Jayapura City Regional Regulation which favors the Youtefa Bay sea shellfish seekers as indigenous peoples related to the ecofeminism theory related to the improvement of mangrove forests by the government. The remote sensing method looks at the mangrove forest area of Youtefa Bay in 2022. The direct impact of damage to the mangrove forest and plastic waste in the Youtefa Bay area on the availability of shellfish is still available, while the search for shells in the mangrove forest has difficulties due to the presence of plastic waste stuck in the mangrove trees. washed away when it rains and damaged Youtefa Bay Mangrove Forest according to satellite imagery from the comparison of 2017 to 2022 by (-15%) in order to preserve the area again.